Determination of Risk Factors for Hypertension among Women in Rural Area of Andhra Pradesh, India - Jogdand, Keerti S.; Yerpude , Pravin N. (Current Overview on Disease and Health Research Vol. 6, 2022)
The present study aims to investigate the prevalence of risk factors for hypertension among women in rural area of South India. Due to an increase in longevity and the prevalence of risk factors like obesity, inactivity, and poor food, hypertension is becoming a widespread health issue across the world. A community based cross-sectional study was conducted among 837 women selected from rural area of Andhra Pradesh from January to June 2008. Out of 837 women,22.58 % were hypertensive.The age specific prevalence of hypertension was maximum(50.44%) in the age group > 60 yrs.Risk factors such as family h/o HTN,h/o DM,tobacco use, waist circumference and BMI were significantly associated with hypertension. Problem of hypertension is increasing among rural women so health education strategies should be directed towards rural women also. In urban area IEC activities for prevention and control of hypertension has been started but has not reached the rural area, so health education strategies should be targeted towards rural women.